Economic impact of backyard yam farming on household livelihoods in Delta North agricultural zone, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
The study assessed the economic importance of backyard yam farming among households in the Delta North Agricultural Zone, Nigeria. Multistage random sampling was used to select a total of 385 households across seven Local Government Areas for the study. Data were collected with the use of a structured questionnaire. Descriptive statistics such as frequency count, percentage, mean, gross margin, and multiple regression were used for data analysis. The mean net profit earned by the farmers was ₦151,575.93, and the benefit-cost ratio of 2.63 indicated that backyard yam farming is profitable. Its contribution to household income was relatively low, averaging 15.2%, which suggests complementarity in livelihood. The significant determinants of income were farm size (β = 0.725, p-value